ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 135/PUU/XXII/2024 DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILU - NIM. A1012211199, HERMANTO (Jurnal Fatwa Hukum, 2025)
Abstract This study aims to determine the authority of the Constitutional Court in the Constitutional Court Decision Number 135/PUU/XXII/2024 concerning the Separation of National Elections and Local Elections and the impact of the Constitutional Court Decision Number 135/PUU/XXII/2024 concerning the Separation of National Elections and Local Elections. Related to the nature of the decision which is final and binding as mandated by the constitution, it implies that the Constitutional Court is the only judicial institution in Indonesia that does not accommodate a hierarchical judicial process. The final nature of the Constitutional Court decision means that there are no other legal remedies that can be taken by the justiciable. The method used in this study is the normative method. Normative legal research is legal research on secondary data in the form of library research which is carried out by examining library materials in the form of primary, secondary, and tertiary data. Based on the research findings, it was found that the Constitutional Court's authority in Decision Number 135/PUU/XXII/2024 reflects the Court's tendency to transform from a negative legislator to a positive legislator. Originally, the Constitutional Court was only authorized to review the constitutionality of laws against the 1945 Constitution. However, in practice, the Court has become increasingly active in establishing new norms that should fall within the legislative purview. The Court not only declared the unification of national and local elections unconstitutional, but also stipulated that local elections must be held two to two and a half years after the inauguration of the president and members of the House of Representatives (DPR/DPD). The impact of Decision Number 135/PUU/XXII/2024 concerning the Separation of National and Local Elections will impact many regulations that have previously served as the basis for election implementation. Therefore, legal and policy adjustments, as well as active coordination with the legislature and election organizers, are required. Keywords: Decision, Constitutional Court, Separation of Elections Abstrak Penelitian ini bertujuan untuk mengetahui kewenangan mahkamah konstitusi dalam Putusan Mahkamah Konstitusi Nomor 135/PUU/XXII/2024 Tentang Pemisahan Pemilu Nasional Dan Pemilu Lokal dan dampak dari Putusan Mahkamah Konstitusi Nomor 135/PUU/XXII/2024 Tentang Pemisahan Pemilu Nasional Dan Pemilu Lokal. Terkait sifat putusan yang bersifat terakhir dan mengikat (binding) sebagaimana yang diamanahkan konstitusi, mengimplikasikan Mahkamah Konstitusi menjadi satu-satunya lembaga peradilan di Indonesia yang tidak mengakomodir proses peradilan berjenjang. Putusan Mahkamah Konstitusi yang bersifat final diartikan bahwa tidak ada lagi upaya hukum lain yang dapat ditempuh oleh para yustisiabel. Metode yang digunakan dalam penelitian ini adalah metode normatif. Penelitian hukum normatif adalah penelitian hukum terhadap data sekunder berupa penelitian kepustakaan (library research) yang dilakukan dengan cara meneliti bahan kepustakaan yang berupa data primer, sekunder, dan tersier. Berdasarkan hasil penelitian ditemukan bahwa Kewenangan Mahkamah Konstitusi dalam Putusan Mahkamah Konstitusi Nomor 135/PUU/XXII/2024 ini mencerminkan kecenderungan Mahkamah bertransformasi dari negative legislator menjadi positive legislator. Asalnya, MK hanya diberi kewenangan untuk menguji konstitusionalitas undang-undang terhadap UUD 1945. Tapi praktiknya, Mahkamah kian aktif menetapkan norma baru yang seharusnya berada dalam wilayah kerja legislatif. Mahkamah tidak hanya menyatakan bahwa penyatuan pemilu nasional dan lokal inkonstitusional, tetapi juga menetapkan secara normatif bahwa pelaksanaan pemilu lokal harus dilakukan dua hingga dua setengah tahun setelah pelantikan presiden dan anggota DPR/DPD. Dampak dari Putusan Mahkamah Konstitusi Nomor 135/PUU/XXII/2024 Tentang Pemisahan Pemilu Nasional Dan Pemilu Lokal akan berpengaruh terhadap banyak regulasi yang selama ini menjadi dasar pelaksanaan pemilihan. Karena itu, diperlukan penyesuaian hukum dan kebijakan, serta koordinasi aktif dengan legislatif dan penyelenggara pemilu. Kata Kunci : Putusan, Mahkamah Konstitusi, Pemisahan Pemilu